2018
DOI: 10.5114/aic.2018.79865
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in men and women with ST-segment elevation myocardial infarction and incomplete infarct-related artery flow restoration: a multicenter national registry

Abstract: IntroductionLittle is known about gender-related differences in ST-segment elevation myocardial infarction (STEMI) and incomplete infarct-related artery (IRA) reperfusion after primary percutaneous coronary intervention (pPCI).AimTo evaluate gender-related differences in clinical characteristics and prognosis in patients with STEMI and incomplete IRA reperfusion after pPCI.Material and methodsFrom 42,752 STEMI patients hospitalized between 2009 and 2011 in Poland we analyzed a group of 984 (36%) females and 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…In our study, when comparing the presentation of STEMI in relation to gender, we found that women were elderly, had a significantly higher prevalence of comorbidities (obesity, diabetes mellitus and hypertension) and poor hospital outcomes (higher rates of pulmonary edema, mechanical ventilation and even in-hospital mortality), suggesting a greater severity in the clinical presentation for this group. These findings were similar to different studies from different regions [ 9 – 13 ]. Also a recent study conducted from six Middle Eastern Countries demonstrated that women have almost doubled the number of mortality from STEMI compared with men [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, when comparing the presentation of STEMI in relation to gender, we found that women were elderly, had a significantly higher prevalence of comorbidities (obesity, diabetes mellitus and hypertension) and poor hospital outcomes (higher rates of pulmonary edema, mechanical ventilation and even in-hospital mortality), suggesting a greater severity in the clinical presentation for this group. These findings were similar to different studies from different regions [ 9 – 13 ]. Also a recent study conducted from six Middle Eastern Countries demonstrated that women have almost doubled the number of mortality from STEMI compared with men [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies of various nature have also reported the same observation of relatively or significantly higher rate of adverse outcomes among women. 4,5,8,9,12,13,15,22,25 However, differences in outcomes was suspected to be driven by the fact that female patients had more high risk clinical profile as compared to male patients, which included older age, more diabetic, more hypertensive, more obese, and prolonged exposure to the untreated ischemia. Therefore, female patients were compared to the propensity matched cohort of male patients which showed that the apparent difference by gender in in-hospital mortality rate diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found female gender to be associated with a significant increased risk of shortand long-term mortality after acute coronary event. [4][5][6][7][8][9][10][11][12][13] Nonetheless, there exist a conflict of evidence as ample literature also available suggesting either no gender differences in outcomes or attributing differences in outcomes with differences in baseline characteristics or increased burden of comorbidities in women due to relatively older age at presentation. 14,15 Studies reporting gender disparities in outcomes postulated various determinants of higher rate of adverse events in women, some studies argued that the atypical clinical presentation is more common among women also pre-hospital delay is more common for females as compared to their male counterpart resulting in delay in reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Other studies focusing on STEMI with gender difference have also shown this phenomenon. 17,18 The possible causes include older age and more comorbidities in female patients with ACS. However, a further study on STEMI in younger patients showed worse short-term outcomes in female patients after adjustment for demographics, comorbidities, medications, and severity of coronary disease.…”
Section: Discussionmentioning
confidence: 99%